A fencing robot for performance testing in elite fencers - Weichenberger, M.; Schilling-Kästle, V.; Mentz, L.; Engleder, T.; Hessling, M. (Sports Technology, 2015)
Performance testing in fencing is only meaningful in combination with fast and complex movement demands for the tested athlete. Therefore, a fencing robot has been developed in cooperation with the German Fencing Federation and the national fencing team that can perform fast movements back and forth. It has 10 LED target areas distributed over its body which represent visual signals to start the fencing attack. The duration of time to hit the target area is measured. The robot's front arm is motorized to parry expected attacks of the fencer. Through pre-defined programs, where back and forth movement of the robot, moment of visual attack signals and movement of the weapon arm are set, a realistic and reproducible combat situation is provided. Several safety measures like ultrasonic range finders and electric safety edges are installed in the front and the rear to prevent the athlete or the surrounding of a collision. The fencing robot is integrated in a complex performance test to analyze speed, endurance, tactics, and technique in elite fencers. http://www.hs-ulm.de/users/hessling/_downloads/Video%20Fencing%20Robot.MP4.